Otomotif Disaat Masa Pandemi Covid-19 Dengan Model Altman Z-Score - Irvan Rizky Septian; Muhammad Zamzami; Saepul Ridwan; Fetiana Pristianti; Elisabet Anandaputri; Yanuar Ramadhan (AKUNTANSI 45, 2024)
This study aims to ascertain the financial condition and anticipate bankruptcy of several automotive industry companies during the Covid-19 outbreak. PT Astra International Tbk, PT Indomobil Sukses Internasional Tbk, PT Gajah Tunggal Tbk, and PT Astra Otoparts Tbk became the population in this study. This study also describes the company’s financial performance, analyzes financial ratios to distinguish healthy and unhealthy companies, and determines how the company’s financial performance and health in 2020-2022. Primary data is the company’s financial statements from 2020-2022. Secondary data are journals and articles that support this research. The research method is a quantitative method based on the formulas in the Altman Z-Score theory. The results showed that the financial condition of these companies was not always stable from year to year during the pandemic.